Enhanced Recovery after Intensive Care (ERIC): study protocol for a German stepped wedge cluster randomised controlled trial to evaluate the effectiveness of a critical care telehealth program on process quality and functional outcomes. Issue 9 (25th September 2020) - Adrion, Christine; Weiss, Bjoern; Paul, Nicolas; Berger, Elke; Busse, Reinhard; Marschall, Ursula; Caumanns, Jörg; Rosseau, Simone; Mansmann, Ulrich; Spies, Claudia
Abstract : Introduction: Survival after critical illness has noticeably improved over the last decades due to advances in critical care medicine. Besides, there is an increasing number of elderly patients with chronic diseases being treated in the intensive care unit (ICU). More than half of the survivors of critical illness suffer from medium-term or long-term cognitive, psychological and/or physical impairments after ICU discharge, which is recognised as post-intensive care syndrome (PICS). There are evidence-based and consensus-based quality indicators (QIs) in intensive care medicine, which have a positive influence on patients' long-term outcomes if adhered to. Methods and analysis: The protocol of a multicentre, pragmatic, stepped wedge cluster randomised controlled, quality improvement trial is presented. During 3 predefined steps, 12 academic hospitals in Berlin and Brandenburg, Germany, are randomly selected to move in a one-way crossover from the control to the intervention condition. After a multifactorial training programme on QIs and clinical outcomes for site personnel, ICUs will receive an adapted, interprofessional protocol for a complex telehealth intervention comprising of daily telemedical rounds at ICU. The targeted sample size is 1431 patients. The primary objective of this trial is to evaluate the effectiveness of the intervention on the adherence to eight QIs daily measured during the patient's ICU stay, compared with standard of care. Furthermore, the impact on long-term recovery such as PICS-related, patient-centred outcomes including health-related quality of life, mental health, clinical assessments of cognition and physical function, all-cause mortality and cost-effectiveness 3 and 6 months after ICU discharge will be evaluated. Ethics and dissemination: This protocol was approved by the ethics committee of the Charité—Universitätsmedizin, Berlin, Germany (EA1/006/18). The results will be published in a peer-reviewed scientific journal and presented at international conferences. Study findings will also be disseminated via the website (www.eric-projekt.net ). Trial registration number: ClinicalTrials.gov Registry (NCT03671447 ).